Responsible use of antibiotics in aquaculture - Serrano, Hernandez Pilar (FAO, 2005)
Considering the misuse of antibiotics, this document aims to raise awareness of the antibiotic resistance problem in fish farming and related sectors, and promote the use of these drugs according to the FAO Code of Conduct for Responsible Fisheries. It focuses on antibiotics misuse and the concomitant threat of resistance development.